BAFIA KAMEROEN and YAKA-MUZIEK Nos. 7 and 8 in a series of African music recordings issued by the Musee Royale de l'Afrique Centrale, Tervuren, Belgium and the Belgische Radio en Televisie, 1972. 12" L.P. with booklet in four languages, pp. 49 and 60 - Merriam, Alan P. (International Library of African Music, 1973)
pages: 103-104
Keywords: African Music